Kerion celsi caused by Trichophyton tonsurans in an adult - Jacqueline Paulina Aguirre Sotelo; Víctor Manuel Tarango Martinez; Lucio Vera Cabrera (Sociedade Brasileira de Dermatologia, 2022)
Abstract Tinea capitis is an uncommon infection in adults, and predominantly affects women and the elderly with hormonal disorders and immunosuppression. Clinical features are often polymorphic and atypical. A kerion celsi case in an elderly female patient with type 2 diabetes mellitus and menopause is presented. The diagnosis was established by direct examination and the isolation of Trichophyton tonsurans in culture and typified by microculture. Treatment with prednisone and itraconazol was very successful. Recognizing the presentation of tinea capitis in adults will help clinicians to avoid delay in the diagnosis, awareness of the risk factors and provide early treatment to minimize sequelae of the disease.